Penerapan Media Game Edukatif dalam Pembelajaran PAI untuk Meningkatkan Motivasi Belajar Siswa Kelas VIII A SMPIT Al-Jabar Karawang - Nayla Nur Zahrania; Puti Rasina Mianti; Putri Andina Aminarti; Muhammad Ifan Fatihah; Muhammad Fatih Dhiya UL Haqsyah; Muhammad Rayhan Sanabil (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Learning motivation plays an essential role in attaining academic success for students. Junior high school learners frequently find Islamic Religious Education challenging because of the difficult content and their limited interest in the subject. This research intends to investigate how the use of educational games influences student motivation in learning this subject. The findings of the research indicated that utilizing educational games could greatly enhance students' motivation to learn. Those who engaged in this method demonstrated a higher degree of motivation. Furthermore, the test results related to their comprehension of Islamic Religious Education also showed a notable improvement among the eighth-grade students at SMP Al-Jabar Karawang.